Highly Sensitive Thin‐Film Sensing with a Toroidal Dipole Resonance in the Midinfrared Supported by an E‐Shaped Germanium Metasurface. Issue 11 (26th June 2022) - Sun, Min; Wang, Guangdong; Shi, Yuechun; Han, Zhanghua
Abstract : Optical sensing applications based on resonant structures always demand on novel optical resonances with large quality factors to achieve high sensitivities. Herein, it is experimentally demonstrated that a toroidal dipole (TD) response working in the midinfrared, supported by a metasurface structure composed of E‐shaped germanium elements on a CaF2 substrate, can be harnessed to achieve high‐performance optical sensors. By elaborately designing the geometrical parameters of the E‐shaped element, a TD resonance can be supported, which is verified by multipole decomposition of the scattering spectrum. Thin films of polymethyl methacrylate (PMMA) with different thicknesses coated on top of the metasurface structures are used as an example to demonstrate the sensing characteristics of the TD resonance. Both numerical and experimental results show that the TD spectral position is highly dependent on the PMMA thickness and a minimum measurable thickness below 10 nm can be steadily achieved. The results demonstrate that the use of TD resonances provides an effective and viable approach for thin‐film sensing, which may find broad applications in biological and medical diagnosis. Abstract : A novel and highly efficient optical thin‐film sensing technique based on the use of toroidal dipole (TD) resonance is demonstrated with both experimental results and numerical assistance. Supported by an E‐shaped germanium metasurface structure on a CaF2 substrate, the sharp TD resonance working in the midinfrared can help achieve easy detection of PMMA thickness below 10 nm.